The Influence of Problem Based Learning Learning Model on Class IV Social Studies Learning Outcomes at SDN Inpres Tammu-Tammu Maros Regency - Megawati Megawati; Nursalam Nursalam; Muhajir Muhajir (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this study was to determine the description of the learning model, learning outcomes and the effect of the Problem Based Learning (PBL) learning model on the ability to cooperate and social studies learning outcomes for fourth grade students of SDN Inpres Tammu-tammu, Maros Regency. This study uses a quasi-experimental method with a non-equivalent control group design. Data collection techniques through learning outcomes tests, observation and documentation. The data analysis technique used was descriptive statistical analysis, inferential statistical analysis and hypothesis testing. The data obtained were normally distributed and homogeneous using the normality test and the SPSS homogeneity test.The application of the Problem Based Learning learning model in this study obtained the results of the Cooperation ability and social studies learning outcomes for fourth grade elementary school students in Moncongloe District in the high category and experienced an increase after So there was an effect of using the Problem Based Learning model learning model on Cooperation and fourth grade student learning outcomes. in Moncongloe District, it was proven through calculations using the t-test (paired sample t-test) which obtained significant results (2-tailed) 0.000 for the ability to cooperate and learning outcomes. If the significance value is less than 0.05 then Ho is rejected and Ha is accepted. Because the value of 0.00 is smaller than 0.05, Ha in this study is accepted, which means that there is a significant effect on cooperation and social studies learning outcomes for fourth grade elementary school students in Moncongloe District, Maros Regency.